Seaport Building, Management and the Challenges of Sustainability - Owoputi, Adetose Emmanuel; Owoputi, Owolabi Oluwatosin (Archives of Business Research, 2022)
Seaport remains the most feasible for the activities of terminals, international export and import business activities where loading and offloading of inter-land distribution through inland waterways, rail, road and air to ensure that what comes in or go out are checked to meet the national and international rules and regulation guiding seaport operations. As a source of major point of commercial activity along the coast. As a source of pollution, harbors need to be strategically located to provide the greatest benefit according to economic and environmental issues. The marine environment and its effects on ports design, port warehousing, port operation, port hydraulics, coastal geomorphology, littoral drift and sedimentation, port security and safety for shipping technology and economics activities, design and construction of a floating port related structure and other environmental issues. Seaport building must have the organizational capacities to appropriately perceive issues, analysis information about complex economic and environmental relationships factors of turbulent transition, increasing demand on ports to acquire, assimilate, highly fragmented information about new potential constraints and opportunities in port management and challenges of it sustainability. The geotechnical and Structural aspect of the port construction have been given very little attention. This research use an annotated conversation and questioner to address the above issues, with the aim to apply concepts of practice, port elements and their effects on seaports. This research use an annotated conversation and questioner to address the above issues, and their effects on seaports. This research have to investigate the needed professionals, in civil, structural , geotechnical, hydraulic engineers and consultants to strength the usage of modern materials, corrosion, naval-architecture and other input knowledges of which is required to produce a sound and commercial design of a modern standard seaport or marine terminal for sustainability.